2017
DOI: 10.1038/oncsis.2016.90
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-activating factor (PAF) receptor as a promising target for cancer cell repopulation after radiotherapy

Abstract: A major drawback of radiotherapy is the accelerated growth of the surviving tumor cells. Radiotherapy generates a variety of lipids that bind to the receptor for platelet-activating factor, expressed by cells in the tumor microenvironment. In the present study, using the TC-1 tumor cell line, we found that irradiation induced a twofold increase in receptor expression and generated agonists of receptor. Irradiated cells induced a 20-fold increase in live TC-1 proliferation in vitro. Furthermore, subcutaneous co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
62
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(74 citation statements)
references
References 34 publications
7
62
0
5
Order By: Relevance
“…All these factors have been shown to promote recruitment of monocytes and induction of M2 phenotype at the tumor site . Interestingly, M2 phenotype may also be induced by chemotherapy and by‐products of chemotherapy, such as PAFR ligands (platelet‐activating factor receptor ligands), further promoting tumor cell repopulation and growth . Besides, tumor cell metabolites may also control Mϕ phenotype.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All these factors have been shown to promote recruitment of monocytes and induction of M2 phenotype at the tumor site . Interestingly, M2 phenotype may also be induced by chemotherapy and by‐products of chemotherapy, such as PAFR ligands (platelet‐activating factor receptor ligands), further promoting tumor cell repopulation and growth . Besides, tumor cell metabolites may also control Mϕ phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Interestingly, M2 phenotype may also be induced by chemotherapy and by-products of chemotherapy, such as PAFR ligands (platelet-activating factor receptor ligands), further promoting tumor cell repopulation and growth. 12,13 Besides, tumor cell metabolites may also control M phenotype. Selleri and co-workers showed that lactate, secreted by mesenchymal stromal cells, skewed GM-CSF/IL-4 driven dendritic cells maturation from monocytes to M2 M s. 14 In a similar fashion, Colegio and co-workers showed that lactate can promote M2 M phenotype through hypoxia induced factor-1 (HIF-1 ) stabilization.…”
Section: Introductionmentioning
confidence: 99%
“…Eicosanoids are derived from arachidonic acid and are pivotal regulators of inflammatory responses (21). Chemotherapy or irradiation stimulates the release of tumor-promoting lipid mediators, including prostaglandins, platelet-activating factor, sphingosine-1-phosphate (S1P), ceramide-1-phosphate (C1P), and lysophosphatidic acid into the tumor microenvironment (5,19,22,23). Chemotherapy has been recently reported to stimulate the proliferation of ovarian cancer cells through a caspase-3-mediated arachidonic acid pathway (24).…”
mentioning
confidence: 99%
“…PAF is a potent pro-inflammatory phospholipid and thus plays roles in many diseases, including anaphylaxis, sepsis, acute respiratory distress syn-drome, bronchial asthma, and G-protein-coupled PAF receptor (PAFR) mediated inflammatory signals [1,5,7]. PAF also promotes neovascularization [4] and tumorgenesis [8]. The deletion of VLDLR in mice not only causes hair loss phenotype on the skin of lactating pups [6], but also leads to severe neovascularization in retina [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…PAFAH, a target of VLDLR signal, hydrolyzes PAF and protects the PAF-mediated inflammation in the skin of pups [6]. PAF binding to PAF receptor activates many physiological events including inflammation, angiogenesis and tumorgenesis [4,7,8]. PAF signal balance can be elaborately regulated by controlling PAF production, PAF hydrolyzation and PAF/PAF receptor pathways [7].…”
Section: Ivyspringmentioning
confidence: 99%